2014
DOI: 10.1039/c4em00307a
|View full text |Cite
|
Sign up to set email alerts
|

Organic aerosols and inorganic species from post-harvest agricultural-waste burning emissions over northern India: impact on mass absorption efficiency of elemental carbon

Abstract: Atmospheric PM2.5 (particulate matter with aerodynamic diameter of ≤ 2.5 μm), collected from a source region [Patiala: 30.2 °N; 76.3 °E; 250 m above mean sea level] of emissions from post-harvest agricultural-waste (paddy-residue) burning in the Indo-Gangetic Plain (IGP), North India, has been studied for its chemical composition and impact on regional atmospheric radiative forcing. On average, organic aerosol mass accounts for 63% of PM2.5, whereas the contribution of elemental carbon (EC) is ∼3.5%. Sulphate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…9b). During the paddy residue burning emission in IGP, a previous study has reported average NH 4 + -to-SO 4 2− equivalent ratio of 1.3 and NO 3 − /SO 4 2− mass ratio of 0.61 (Rajput et al 2014c). The average NO 3 − /SO 4 2− mass ratio < 1 can be attributed to predominant impact from stationary source/s (biomass burning, coal combustion and industrial emission), whereas the NO 3 − /SO 4 2− mass ratio ≥ 1 indicates predominant impact from mobile source (vehicular emissions) (Wu et al 2017).…”
Section: Inferences From Anthropogenic Inorganic Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…9b). During the paddy residue burning emission in IGP, a previous study has reported average NH 4 + -to-SO 4 2− equivalent ratio of 1.3 and NO 3 − /SO 4 2− mass ratio of 0.61 (Rajput et al 2014c). The average NO 3 − /SO 4 2− mass ratio < 1 can be attributed to predominant impact from stationary source/s (biomass burning, coal combustion and industrial emission), whereas the NO 3 − /SO 4 2− mass ratio ≥ 1 indicates predominant impact from mobile source (vehicular emissions) (Wu et al 2017).…”
Section: Inferences From Anthropogenic Inorganic Speciesmentioning
confidence: 99%
“…Furthermore, several aerosol punches (n = 15) were de-carbonated in HCl fumes for assessing the peak positioning and quantifying the content of carbonate carbon (CC) in the sample (Cachier et al 1989). Area under the CC peak in thermograph was integrated manually and corrected for OC concentrations in aerosols as reported in an earlier publication (Rajput et al 2014c). Filter-based blank concentrations of OC (3.6 ± 0.6 μg/cm 2 ; n = 6) has been determined and the average value was subtracted from the measured concentration in aerosol samples, after normalizing to the full-filter area.…”
Section: Determination Of Aerosol Mass and Ec-oc Analysismentioning
confidence: 99%
“…Previous studies have made attempts to highlight the source regions of large-scale biomass burning emissions in upwind IGP (Rengarajan et al, 2007;Rajput et al, 2011Rajput et al, , 2014c. Temporal variability and emission budget from upwind IGP further suggests that biomass (post-harvest agriculturalwaste and bio-fuels) burning emission is a predominant source of fine-mode aerosols on an annual and seasonal basis (Rajput et al, 2014a(Rajput et al, , 2014bRastogi et al, 2014;Singh et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, higher concentrations of levoglucosan and other biomarkers were present in emissions from this source, although no unique marker species were identified among those reported in Table 3. These data expand both the number and chemical detail of prior emissions 5 measurements of agricultural fires in the IGP (Rajput et al, 2014a;Rajput et al, 2014b;Singh et al, 2014).…”
mentioning
confidence: 99%